2008
DOI: 10.1017/s1049023x00006415
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Laser Spectroscopy as a Screening Tool for Detecting Hematoma in Patients with Head Trauma

Abstract: Introduction:Among imaging techniques, computed tomography (CT) is a reliable method for detecting intracranial hematomas in patients with head trauma, but it is not generally available in special circumstances like prehospital situations and harsh conditions such as those following an earthquake.Objective:The objective of this study is to determine if near-infrared spectroscopy (NIRS) is useful for performing CT scans on patients with closed head trauma that present to medical centers that do not have the abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…It can also detect and localize intracranial hematomas (Gopinath, Robertson, Grossman, & Chance, ) as well as provide continuous, non‐invasive measurement of cerebral hemodynamic and metabolic parameters over multiple regions of interest. Ghalenoui et al () for instance, studied 142 patients with closed‐head injuries. The sensitivity and the specificity of an NIRS for detecting intracranial hematomas was 88.9% and 77.7%, respectively.…”
Section: Diagnostic Modalitiesmentioning
confidence: 99%
“…It can also detect and localize intracranial hematomas (Gopinath, Robertson, Grossman, & Chance, ) as well as provide continuous, non‐invasive measurement of cerebral hemodynamic and metabolic parameters over multiple regions of interest. Ghalenoui et al () for instance, studied 142 patients with closed‐head injuries. The sensitivity and the specificity of an NIRS for detecting intracranial hematomas was 88.9% and 77.7%, respectively.…”
Section: Diagnostic Modalitiesmentioning
confidence: 99%
“…Although routinely performed in most 'Western' countries, CT/MRI may not be available to all acute stroke patients worldwide. Hence, less cost-intensive techniques-including optical imaging (OI)-have been probed as a screening tool for intracerebral haemorrhage [15]. However, the most decisive differential diagnosis, hypertensive intracerebral haemorrhage, is typically located in the deeper parts of the brain [16], and is thus not directly accessible to non-invasive OI.…”
Section: (A) the Acute Stage Of Strokementioning
confidence: 99%
“…In 2008, Ghalenoui et al 7 published a prospective observational study in which they evaluated 148 patients admitted to a hospital in Iran with head injuries with both CT and NIRS. They found that NIRS found 46.6% of the admitted patients to possibly have intracranial hematoma, while CT scan determined that the true number of patients with intracranial hematoma was actually 36.5%.…”
Section: Introductionmentioning
confidence: 99%